Experiences of family members of adult children in forensic services and their interactions with mental health professionals - Finlay-Carruthers, Gemma (2016)
The importance of family caregiver involvement in (secure) mental health services has been increasingly recognised and there is a wide consensus that family caregivers should be seen by clinicians as partners in the care of patients (Harvey & Ramsay, 2004). Mental health carers however, especially those caring for relatives who are subject to compulsory care and treatment, often feel overlooked and marginalised, caring in complex circumstances with little or no support. This thesis focuses specifically on the views and experiences of parents of adult children in forensic mental health services. A structured review and synthesis of qualitative studies was undertaken to develop insight into the perceived level of involvement in care, from the perspective of family members of mental health service users. The review also examines family carers’ relationships and engagement with mental health professionals. This highlighted that the practices of some professionals contribute to the distress experienced by caregivers in this marginalised group. The empirical research study, employed a qualitative design conducted within the framework of IPA, and explored what it is like for parents with an adult son or daughter with mental illness and offending background detained in a regional medium secure unit. Findings indicated that parents’ experiences were characterised by a strained relationship with mental health services, accompanied by practical difficulties in getting help in the first place, and conflicting emotions felt in response to their unwell family member’s continued detention in the forensic care setting. Following on from this, a case study describes brief family psycho-education in secure care and illustrates how staff in forensic services can collaborate with parents more empathetically and effectively. Afterwards, the Family Relations Test, an instrument that assesses affective relations from the child’s perspective is critically reviewed. The utility of this tool in clinical practice is remarked upon. In the concluding chapter, the ways in which service delivery and research can be influenced by ‘giving a voice’ to parents of forensic clients is explored, and implications of the findings are discussed with reference to the current recognition of family and social inclusion.